2016
DOI: 10.1071/ah15157
|View full text |Cite
|
Sign up to set email alerts
|

Flying blind: trying to find solutions to Indigenous oral health

Abstract: Objective. The aim of the present study was to identify all published evidence about oral health in Indigenous children in Australia and to determine trends in Indigenous oral health over time.Methods. PubMed was used to search for published peer-reviewed articles that reported caries (decay) prevalence rates and/or caries experience (based on caries indices) in Indigenous children. Studies included in the analysis needed to report clinical oral health data (not self-reported dental experiences), and articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 30 publications
2
17
1
Order By: Relevance
“…In this study we aimed to understand from the perspective of urban Indigenous parents and carers how child oral health was impacting on their family life. According to national statistics [9], Indigenous Australians of all ages experience worse oral health outcomes than non-Indigenous Australians, yet there are few data that explores oral health from an Indigenous Australian personal perspective [9]. We found that oral health was an important issue for urban Indigenous families and maintaining oral health to a desired standard was impacting mothers and their families.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this study we aimed to understand from the perspective of urban Indigenous parents and carers how child oral health was impacting on their family life. According to national statistics [9], Indigenous Australians of all ages experience worse oral health outcomes than non-Indigenous Australians, yet there are few data that explores oral health from an Indigenous Australian personal perspective [9]. We found that oral health was an important issue for urban Indigenous families and maintaining oral health to a desired standard was impacting mothers and their families.…”
Section: Discussionmentioning
confidence: 85%
“…Within Australia, Aboriginal and Torres Strait Islander (hereafter respectfully referred to as Indigenous) children experience worse oral health than non-Indigenous children [9]. Indigenous children experience more caries, are twice as likely to be hospitalised for oral health problems and are more likely to require extraction and receive general anaesthetic than non-Indigenous children [10].…”
Section: Introductionmentioning
confidence: 99%
“…38 The present review has identified that the data available for the oral health of Indigenous adults living throughout Australia are more limited than those available for Indigenous children. This is despite approximately one-third of Indigenous people attending the public oral healthcare system.…”
Section: Indigenous Oral Health Australian Health Reviewmentioning
confidence: 99%
“…Reasons for these differences are multifactorial including socioeconomic disadvantage, poor access to health services, poor nutrition, heavy use of alcohol and smoking and genetic variations [4]. Similarly, Indigenous Australian children experience worse oral health than non-Indigenous children [5]. Regardless of many efforts, health inequalities, including oral health, between Indigenous and non-Indigenous Australians have remained for decades [6].…”
Section: Introductionmentioning
confidence: 99%